2014
DOI: 10.1186/1471-2148-14-52
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of holometabolous insects inferred from transcriptome-based phylogeny and comprehensive morphological data

Abstract: BackgroundDespite considerable progress in systematics, a comprehensive scenario of the evolution of phenotypic characters in the mega-diverse Holometabola based on a solid phylogenetic hypothesis was still missing. We addressed this issue by de novo sequencing transcriptome libraries of representatives of all orders of holometabolan insects (13 species in total) and by using a previously published extensive morphological dataset. We tested competing phylogenetic hypotheses by analyzing various specifically de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
184
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(209 citation statements)
references
References 53 publications
22
184
2
1
Order By: Relevance
“…Phylogenomic data sets now confirm the monophyly of Pycnogonida, Euchelicerata, Myriapoda, and Mandibulata, and within the latter clade, firmly places the Hexapoda (Insects) within the Tetraconata or Pancrustacea, a view that challenges earlier classifications that would maintain traditional boundaries among major arthropod classes, but is as yet unresolved with respect to the best supported pancrustacean sister-clade for Hexapoda (Giribet and Edgecombe, 2012;Oakley et al, 2013). Insect order-level phylogeny has seen rapid clarification of long-standing controversies over the relationships of the earliest extant insect lineages, the origin of winged insects, the relationships among the polyneopteran orders, and the origin and relationships of the holometabolan orders (Misof et al, 2014;Peters et al, 2014). While these new datasets are enormous and emphasize genetic evidence, their interpretation and analysis in the context of morphological and macroevolutionary evidence provides an example of how data combination and integration of multiple sources of evidence can flourish in a fully integrated phylogenomic research program.…”
Section: Gene (Or Protein) Sequences Of Selected Sets Of Genesmentioning
confidence: 99%
“…Phylogenomic data sets now confirm the monophyly of Pycnogonida, Euchelicerata, Myriapoda, and Mandibulata, and within the latter clade, firmly places the Hexapoda (Insects) within the Tetraconata or Pancrustacea, a view that challenges earlier classifications that would maintain traditional boundaries among major arthropod classes, but is as yet unresolved with respect to the best supported pancrustacean sister-clade for Hexapoda (Giribet and Edgecombe, 2012;Oakley et al, 2013). Insect order-level phylogeny has seen rapid clarification of long-standing controversies over the relationships of the earliest extant insect lineages, the origin of winged insects, the relationships among the polyneopteran orders, and the origin and relationships of the holometabolan orders (Misof et al, 2014;Peters et al, 2014). While these new datasets are enormous and emphasize genetic evidence, their interpretation and analysis in the context of morphological and macroevolutionary evidence provides an example of how data combination and integration of multiple sources of evidence can flourish in a fully integrated phylogenomic research program.…”
Section: Gene (Or Protein) Sequences Of Selected Sets Of Genesmentioning
confidence: 99%
“…(150-140 Mya) (Sukatsheva and Rasnitsyn, 1992), the Boreidae are thought to be at least Late Jurassic in origin, suggesting the possibility that the flea stem lineage is equally old. Recent molecular studies however have suggested that Siphonaptera and Mecoptera are sister groups (McKenna and Farrell, 2010;Misof et al, 2014;Peters et al, 2014;Wiegmann et al, 2009), Divergence time analysis on holometabolous insects with limited taxonomic representation of Siphonaptera placed the split of Mecoptera and Siphonaptera into the Triassic (Wiegmann et al, 2009) or the Jurassic , well within the age range of the recently proposed fossil ''fleas''.…”
Section: Introductionmentioning
confidence: 95%
“…New technology-based means of gathering information have added to taxonomic quality control and sophisticated methods of data analysis. In taxonomy, new sources of data-e.g., nano CT-scan (Arillo et al 2015), evo-devo (Minelli 2015), 3D morphology (Khoury et al 2015), transcriptome phylogeny (Peters et al 2014), and cryopreservation centers-add to other sources of information and protocols that keep the biological system sound, including its nomenclature. But here again the new methods do not replace, but complement the traditional, tested methods and procedures (Schlick-Steiner et al 2010).…”
Section: Discussionmentioning
confidence: 99%